Komunikasi Interpersonal Sebagai Kunci Kesuksesan dalam Proses Belajar Mengajar - M. Padeli Wibowo; Raudhatul Jannah; Syakila Pradita; Afwan Syahril (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Interpersonal communication plays a crucial role in creating a conducive and productive learning environment, particularly in the teaching and learning process. A harmonious relationship between teachers and students through effective communication can enhance students' motivation, self-confidence, and engagement in learning while also fostering their character development. This study aims to identify the role of interpersonal communication in supporting the success of the teaching and learning process, addressing existing barriers, and exploring its benefits in character development. The research employs a qualitative method with a library research approach, involving data analysis from scientific journals, books, and relevant documents. The findings reveal that effective interpersonal communication not only impacts students' academic achievements but also contributes to building character values such as empathy, respect, and responsibility. Communication barriers, such as cultural differences, language issues, and lack of communication skills, can be addressed through training, the use of visual aids, and the integration of educational technology. With this approach, interpersonal communication becomes a key element in modern learning processes, both in face-to-face and digital contexts.